ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN PADA CAFE SIESAN DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN TRIZ - Novia, Novia; Milana, Lia (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Consumer satisfaction with service quality at Siesan Cafe is carried out using the Importance Performance Analysis (IPA) and TRIZ methods. Service quality is defined as a large measure of the level of service that can be provided in accordance with the level of consumer expectations. Consumer satisfaction is used to determine the level of customer satisfaction with the quality of products or services provided by the company. Consumer satisfaction is satisfaction. Consumer pleasure is satisfaction using the marketing mix attributes (4P) of products /services, prices /prices, places /places, and promotions /promotions that use average value calculations between consumer perceptions and employee performance, GAP values, and Cartesian diagrams. The most dominant factor is the product /service, place/place, and promotion/ promotion, wherein because of that service, place, and promotion does not meet the level of consumer perception/desire, so consumers feel less satisfied with the services provided from this value, namely, Products/Services with a percentage of 88.75% (not satisfactory) and a GAP value of -0.2, then there is a price/ price with a percentage of 87.85% (not satisfactory) and a GAP value of -0.5, then a place/place with a percentage of 91 , 83% (not satisfactory) and GAP value -0.4, and the last promotion / promotion with a percentage of 83.75% (not satisfactory) and GAP value -0.6.